Cliford's puppy days - Bridwell, Norman (New York : Scholastic, 1989)
Everybody loves Clifford Now children can have their own Clifford toy to enjoy at playtime and curl up with at bedtime. Cuddly Clifford comes in his very own doghouse with a mini-edition of Clifford's Puppy Days packed right inside.